PENGARUH TEKANAN ANGGARAN WAKTU, SIFAT MACHIAVELLIAN DAN KOMPLEKSITAS TUGAS TERHADAP PERILAKU AUDIT DISFUNGSIONAL - Winanda, I Komang Hendra; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi, 2017)
Dysfunctional behavior in the context of an audit conducted by the deviant behavior of auditors in the implementation of the audit process. Auditor dysfunctional behavioral tendency can be reduced by knowing the causal factors are derived from an individual's internal auditor. The purpose of this study was to test the effect of budget pressure, Machiavellian nature and complexity of the task in dysfunctional behavior auditor. The data collection by used questionnaire. The population in this study is the auditor who worked in public accounting with a total sample of 63 auditors were taken using purposive sampling technique. Technical analysis data used in this research is multiple linear regression analysis. The results showed that the time budget pressure, Machiavellian nature and complexity of the task have positive influence on the behavior of dysfunctional auditor.
Keywords: time budget pressure; Machiavellian nature; the level of complexity of the task; dysfunctional behavior auditor